Wavefront Sensing Based on Partially Occluded and Extended Scene Target - Yang Lv; Haotong Ma; Quan Sun; Pengfei Ma; Yu Ning; Xiaojun Xu (IEEE Photonics Journal)
In order to overcome the shortcomings of traditional wavefront achieving techniques, which cannot capture the wavefront in the case that an obstacle presents in front of the reference source, we propose and demonstrate a new wavefront measuring method by exploiting a plenoptic configuration. By processing the 4-D light-field information captured by plenoptic configuration, the obstacle's information can be distinguished and eliminated, and the preserved scene target's information can be utilized to extract the wavefront information. The numerical simulation using partially occluded and extended scene targets show that this technology is feasible, even in the situation of strong wavefront aberrations. The technology proposed in this paper can have wide applications in astronomical imaging and surveillance systems.